A study of irradiation effects in solids - Brown, Michael Ewart (Rhodes University, Faculty of Science, Department of Chemistry, 1966)
One of the primary objects of this research was to determine, if possible, the nature of the radiation damage prior to thermal decomposition. The X-ray study has not wholly achieved this although more information has been derived from it than from similar work on AgMnO₄ However, the diffuse reflections obtained do indicate, quite strongly, the creation of point defects during irradiation. This is of value since such assumptions have been made in the explanation of the kinetics of decomposition of a number of irradiated solids (BaN₆,CaN₆). In addition the X-ray work has suggested future research which should produce useful information; namely, a precise study of the diffuse reflections. Another object of the research was to attempt to determine what characteristics, if any, of the kinetics of the decomposition of an unirradiated solid would predetermine a marked irradiation effect. It is obvious that the type of nuclear growth which occurs e.g. branching chain, or power law, does not characterise a substance with regard to a possible irradiation effect . The photosensitivity, or otherwise, also does not determine whether there will be an irradiation effect. However, the one property that the substances which have been studied, have in common, is a polyatomic anion, but here again ammonium dichromate does not show an acceleration of the decomposition after irradiation. Consequently it is considered that it is not possible to say, a priori, whether a solid will undergo an accelerated decomposition after irradiation. Each new solid, unless it belongs to a particular class e.g. the alkaline earth azides , must be considered afresh. Nevertheless it does appear that the irradiation effect can take two forms: - (i) the production of an unstable compound e.g. nickel oxalate, the decomposition of which affects the normal pyrolysis; and (ii) the production of point defects which determine the nature of the subsequent thermal decomposition e.g . CaN₆ . It is possible that the effect requires an interaction of the created point defects with the existing line defects.
Keywords: Decomposition (Chemistry); Crystals -- Thermal properties; Oxalates -- Thermal properties; Solids -- Effect of radiation on